John Murray Forbes papers - Forbes, John Murray, 1771-1831.
Letterbook (1817-1818) kept during the time Forbes was American consul residing at Hamburg, Germany, and Copenhagen, Denmark; and a house expense account book (1825-1830). The letters, all written from Copenhagen, relate to political matters, consular affairs, Forbes's financial difficulties, steam engines and steamboats, and financial and legal questions. Also includes a certification (May 1, 1820) naming Forbes as an agent for commerce and seamen in Buenos Aires, Argentina, or Chile. Correspondents include John Quincy Adams, John Cuthbert, John Fisher, James Grant Forbes, William Lee, James Monroe, Charles Murray, and William Shaler.
Lawyer and diplomat.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Cuthbert, John A. -- 1788-1881 -- Correspondence; Fisher, John, -- active 1817 -- Correspondence; Forbes, James G. -- Correspondence; Lee, William, -- 1772-1840 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Murray, Charles, -- active 1817-1818 -- Correspondence; Shaler, William, -- 1778?-1833 -- Correspondence; Consuls -- Denmark -- Copenhagen; Consuls -- Germany -- Hamburg; Diplomatic and consular service, American -- Denmark; Diplomatic and consular service, American -- Germany; Sailors -- Argentina -- Buenos Aires; Sailors -- Chile; Steamboats; Steam-engines.; Buenos Aires (Argentina) -- Commerce; Chile -- Commerce; Denmark -- Politics and government; Diplomats; Lawyers